Effect of Fatigue on Medial Elbow Torque in Baseball Pitchers: A Simulated Game Analysis. Issue 10 (August 2018) - Okoroha, Kelechi R.; Meldau, Jason E.; Lizzio, Vincent A.; Meta, Fabien; Stephens, Jeffrey P.; Moutzouros, Vasilious; Makhni, Eric C.
Background: The incidence of overuse injury to the elbow among baseball pitchers continues to rise, despite extensive efforts at pitch count regulations and emphasis on proper throwing mechanics. Purpose: To determine if the medial elbow experiences increased torque levels as a baseball pitcher fatigues through the course of a simulated game. Study Design: Descriptive laboratory study. Methods: High school and collegiate baseball pitchers were recruited for this simulated game study. Each pitcher completed a simulated game consisting of 6 innings and a standardized pitching scheme of fastballs, curveballs, and changeups. In total, each pitcher threw 90 pitches. Fatigue was reported per inning with a visual analog scale, and pitch velocity was captured per pitch with a radar gun. Outcome measures were assessed with a validated mobile sensor and included medial elbow torque, arm speed, arm rotation, and arm slot. Linear and quadratic regression modeling was used to evaluate the relationship between pitcher fatigue and pitching kinematics. Results: A total of 11 pitchers (mean age, 17.6 years; range, 15-20 years) completed the study. Visual analog scale fatigue scores increased 0.72 points per inning pitched ( P < .01, effect size = 0.64). Medial elbow torque also increased beyond inning 3, with an increase of 0.84 N·m each inning ( P < .01, effect size = 0.08), while pitch velocity decreased (0.28 mph per inning, P < .01, effect size = 0.27). Fastballs generated the greatest amount of medial elbow torque (49.3 ± 1.4 N·m, P < .01, effect size = 0.24). There were no differences in arm rotation ( P = .42) or arm speed ( P = .80) as the game progressed. However, arm slot decreased with each successive inning (0.73° on average per inning, P = .03, effect size = 0.12). No adverse outcomes were noted with use of the mobile sensor. Conclusion: In this simulated game analysis, pitchers experienced increased fatigue after each successive inning. While the average pitch velocity declined with each successive inning, the torque on the medial elbow increased after inning 3. These findings signify a possible relationship between fatigue and injury risk.